2007
DOI: 10.1007/s12030-008-9017-x
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Simulation and Focused Ion Beam Fabrication of Gold Nanostructures for Surface-Enhanced Raman Scattering (SERS)

Abstract: This paper describes the fabrication of gold nanopillar and nanorod arrays and theoretical calculations of electromagnetic fields (EMFs) around ordered arrangements of these nanostructures. The EMFs of both single nanopillars and di-mers of nanopillars - having nanoscale gaps between the two adjacent nanopillars forming the di-mers - are simulated in this work by employing the Finite Difference Time Domain (FDTD) method. In the case of simulations for di-mers of nanopillars, the nano-scale gaps between the nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Due to the well-established strengths of SERS including a lack of photobleaching/photodegradation, the ability to perform multiplexed bioanalysis using a single laser wavelength, and narrow spectral width of Raman bands, the multiplexing capability of Raman and SERS techniques is excellent in comparison to the other spectroscopic alternatives, thus opening new horizons to many applications in medical diagnostics, environmental exposure assessment, drug development and high throughput screening. Improved knowledge of the plasmonics effect and advances in theoretical calculation and simulation studies of the electromagnetic enhancements [33, 5053] will lead to the design and fabrication of plasmonics-active nanostructures with optimal enhancement properties.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the well-established strengths of SERS including a lack of photobleaching/photodegradation, the ability to perform multiplexed bioanalysis using a single laser wavelength, and narrow spectral width of Raman bands, the multiplexing capability of Raman and SERS techniques is excellent in comparison to the other spectroscopic alternatives, thus opening new horizons to many applications in medical diagnostics, environmental exposure assessment, drug development and high throughput screening. Improved knowledge of the plasmonics effect and advances in theoretical calculation and simulation studies of the electromagnetic enhancements [33, 5053] will lead to the design and fabrication of plasmonics-active nanostructures with optimal enhancement properties.…”
Section: Discussionmentioning
confidence: 99%
“…The FDTD software uses the Lorentz-Drude dispersion 5152, 79 model described above in Section 3.1. In the FDTD calculations, a continuous plane wave (633-nm for simulating the laser employed for SERS measurements) propagating in the z direction and having the electric field (E-field) polarized in the x direction was incident on the gold-coated silicon nanowire structures.…”
Section: 0 Results and Discussionmentioning
confidence: 99%
“…This process is also not conducive to fabrication of SERS substrates over a large area, specifically 6-inch wafers. Moreover, the smallest sizes of nano-scale gaps between metallic nano-structures using electron beam lithography and FIB are greater than ~ 10-15 nm 29 . Although SERS based substrates based on disordered metallic nanowires, ordered metallic nanowires, as well as metal-coated silicon or germanium oxide nanowires have been described in the past literature, the ability to reproducibly develop ordered metallic nanowires with controlled sizes, shapes, and sub-10 nm gaps between the nanowires has not been presented previously.…”
Section: Introductionmentioning
confidence: 99%
“…An earlier work in our laboratory has involved the development of planar solid substrates covered with a monolayer of nanospheres that are coated with a thin layer of silver, thus producing a plasmonics-active 2D nanospheres arrays 13 . Recently, Vo-Dinh et al 29 reported the formation of metallic nanostructures on planar substrates and tips of optical fibers by employing focused ion beam milling (FIB). This process is also not conducive to fabrication of SERS substrates over a large area, specifically 6-inch wafers.…”
mentioning
confidence: 99%